Relationship of 137Cs with Fungal Spore Tracers in the Ambient Aerosols from Fukushima after the 2011 Nuclear Accident, East Japan - Kimitaka Kawamura; Bhagawati Kunwar; Kazuyuki Kita; Naho Hayashi; Yasuhito Igarashi (Atmosphere, 2022)
Even after 7 years of the nuclear accident that occurred in 2011 at the Fukushima Dai-ichi nuclear power plant (F1NPP), high levels of 137Cs have been detected in ambient aerosols from some polluted areas of Fukushima. Higher levels of radionuclides were often observed in the atmosphere during and after rain events. We presume that biological processes such as fungal activity associated with higher relative humidity may be involved with a possible emission of radioactivity to the atmosphere, which was originally emitted from the F1NPP accident and was deposited over the ground, forest, soil, etc. Here, we report, for the first time, relationships of 137Cs and organic tracers of fungal spores (i.e., arabitol, mannitol and trehalose) in the aerosol samples collected from Fukushima, Japan. Although we found twice-higher concentrations of 137Cs at nighttime than at daytime, fungal spore tracers did not show a consistent trend to 137Cs, that is, organic tracers at nighttime were similar with those at daytime or were even higher in daytime. This study has not clearly demonstrated that fungal spores are the important source of high levels of 137Cs at nighttime. The current unclear relationship is probably associated with the sampling strategy (four consecutive days with a sampling on/off program for day/nighttime samples) taken in this campaign, which may have caused a complicated meteorological situation.